Thyroglobulin Antibody (TgAb) Positive is an Independent Risk Factor for Lymph Node Metastasis in Patients with Differentiated Thyroid Carcinoma - Lai Y; Gu Y; Yu M; Deng J (International Journal of General Medicine, 2023)
Yeqian Lai, Yihua Gu, Ming Yu, Jiaqin Deng Department of Thyroid Surgery, Meizhou People’s Hospital, Meizhou Academy of Medical Sciences, Meizhou, People’s Republic of ChinaCorrespondence: Yeqian Lai, Department of Thyroid Surgery, Meizhou People’s Hospital, Meizhou Academy of Medical Sciences, No. 63 Huangtang Road, Meijiang District, Meizhou, People’s Republic of China, Email laiyeqian@163.comObjective: To investigate the relationship between lymph node metastasis and the clinicopathologic features of differentiated thyroid carcinoma (DTC) patients with thyroglobulin antibody (TgAb) positive and negative.Methods: A total of 443 patients with DTC were included in this study. Clinicopathological data of the patients were collected, including tumor size, clinical stage, calcification, Hashimoto’s thyroiditis, extra-membrane infiltration, BRAF V600E mutation status, and thyroid-related hormone and antibody levels. The relationship between of lymph node metastasis and clinicopathologic features was analyzed.Results: There were 227(51.2%) TgAb negative and 216(48.8%) TgAb positive DTC patients. Compared with patients without lymph node metastasis, DTC patients with lymph node metastasis had a higher proportion of patients with < 55 years of age, maximum tumor diameter > 1cm, calcification, BRAF V600E mutation, and TgAb positive. Multivariate regression logistic analysis showed that < 55 years old (odds ratio (OR): 2.744, 95% CI: 1.665– 4.522, P< 0.001), maximum tumor diameter > 1cm (OR: 2.163, 95% CI: 1.431– 3.271, P< 0.001), BRAF V600E mutation (OR: 2.489, 95% CI: 1.397– 4.434, P=0.002), and TgAb positive (OR: 1.540, 95% CI: 1.020– 2.326, P=0.040) were risk factors for lymph node metastasis. Maximum tumor diameter > 1cm and BRAF V600E increased the risk by more than one fold for lymph node metastasis in TgAb-negative and TgAb-positive DTC patients.Conclusion: Younger age (< 55 years old), maximum tumor diameter > 1cm, BRAF V600E mutation, and TgAb positive were independent risk factors for lymph node metastasis in DTC. And maximum tumor diameter > 1cm and BRAF V600E mutation were risk factors for lymph node metastasis both in TgAb positive and negative DTC patients.Keywords: differentiated thyroid carcinoma, lymph node metastasis, thyroglobulin antibody, BRAF